Mobile-Based Library Catalog Web Service Development - Fawwaz, Nasya (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
This research centers on the design and development of The Library Catalog mobile application prototype, a novel solution aimed at revolutionizing library catalog systems by adopting a user-centric design framework. The application incorporates critical functionalities, including dynamic search tools, real-time notification systems, and an intuitive navigation structure, to facilitate efficient access to library resources. Key features such as real-time book availability updates, reservation capabilities, and a well-organized menu system encompassing catalog, favorites, search, and profile sections are tailored to meet the fundamental requirements of library users in a digital landscape. The aesthetically pleasing interface, enriched with interactive components like animated notification indicators and distinctive iconography, significantly enhances user engagement and satisfaction. Results from this study indicate that The Library Catalog holds substantial promise in transforming library service delivery by harnessing mobile technology to address the changing needs and expectations of users. The prototype demonstrates a strong potential to streamline access to information and improve the overall library experience. Looking ahead, future development efforts will focus on the full implementation of placeholder features such as advanced search filters, personalized user profiles, and favorite lists, alongside the integration of accessibility options like multilingual support and screen reader compatibility to ensure inclusivity. Additionally, plans include incorporating push notifications for timely updates, conducting extensive user testing for iterative refinement, and exploring seamless integration with existing library management systems to boost scalability and operational efficiency. These enhancements aim to position The Library Catalog as a comprehensive and innovative tool for modern library services in the digital era.